FAKTOR-FAKTOR YANG MEMPENGARUHI PENJUALAN SNACK TORTILLA DUA KELINCI PADA PT. VICTORY JAYATAMA ABADI PEKANBARU - DEHOTMAN, KHORNELIS (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
Abstract: Research conducted at PT. Victory Jayatama Abadi Pekanbaru. Based on the background of the research presented above, the authors can formulate the problem in this study are the factors whether that affects sales Two rabbit tortilla snack products at PT. Grace Niaga Jaya Branch Pekanbaru. The purpose of this study is to knowing factors that affect sales product b circuit at PT. Victory Jayatama Abadi Pekanbaru. Data analysis in this research is done by using method descriptive and quantitative . Method descriptive that is data analysis with way decomposition theories contained in list library and connected with the data obtained from results research that will be collected, grouped and tabulated then taken conclusion. And methods quantitative with technique multiple linear regression. Samples taken in research this is numbered 55, h a sil research is seen from calculation obtained results from test_F from table above show Sig value. A total of 0,000 more small from 0.05%. Or value F hount amount 40.509 Meanwhile value F table could obtained ie N1 = k-1 (6-1 = 5) and N2 = n-k (55-6 = 49) then obtained value F table at N1 = 5 and N2 = 49 such that obtained value F table of 2.40. then could concluded that value F_hount (40.509)> F_table (2.40), so secara together variabel ability sales , conditions markets, capital, conditions organization and other factors have a significant effect to variabel sales biscuits value Adjusted R_Square ofÂ 0.785 means magnitude influence / contribution or contributions made variabel ability sales , conditions markets, capital, conditions organization and other factors amount 78.5 percent while the rest by 21.5 percent affected by other factors that are not sign in in research this.